Concession Bargaining: An Experimental Comparison of Protocols and Time Horizons. (October 2018) - Alberti, Federica; Fischer, Sven; Güth, Werner; Tsutsui, Kei
We test experimentally whether dynamic interaction is crucial for concession bargaining. In our complete information bargaining experiments, two parties with asymmetric conflict payoffs try to agree how to share a commonly known pie by bargaining over a finite number of successive trials (agreement attempts). We compare the fully dynamic interaction to one less dynamic and one static protocol. In the quasi-dynamic protocol, later trials merely reveal that so far no agreement has been reached, and in the static protocol, no feedback information is given about earlier trials. We find that neither conflict rate nor efficiency or inequality of agreements differs across protocols. Comparing different numbers of maximal trials shows that more trials render conflict more likely due to less concessions.